Individual and population variation of linear and non-linear components of the advertisement call of Darwin's frog (Rhinoderma darwinii). Issue 5 (2nd September 2020) - Serrano, José M.; Penna, Mario; Soto-Azat, Claudio
ABSTRACT: Non-linear vocal phenomena (NLP) are complex phonation emissions that include complex frequency patterns, which have been reported in an increasing number of taxa. Such acoustic components may play an important role in signalling individual identity and motivation of emitters. Variations in NLP of distant populations within a species have not been explored in any taxa. Here, we evaluate the variability of Darwin´s frogs ( Rhinoderma darwinii ) advertisement calls at an intra-, inter-population and individual level, and the influence of body size in such variation. The occurrence of non-linear acoustic variables was quantified in 606 advertisement calls, of 38 individuals from three distant populations of R. darwinii in southern Chile. The results indicate that inter-note intervals, dominant frequency and chaos differ among populations and that such differences are likely influenced by body size. In addition, discriminant function analysis (DFA) showed that population variations were strongly supported by dominant frequency, while individual distinctiveness was supported by seven acoustic variables including NLP. For the first time, this study demonstrates how NLP features vary among distant populations of a vertebrate species and contributes with evidence about the influence of body size on individual variation of non-linear vocal components.